Penggantian Kelamin Bagi Transeksual Serta Akibat Hukumnya Menurut Hukum Islam dan Hukum Positif di Indonesia : Studi Komparatif Hukum Islam dan Putusan Pengadilan Nomor 112/Pdt.P/2022/PN Blb - Ainur Rochmah; Dudik Djaja Sidharta; Noenik Soekorini (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Sex reassignment of transsexual individuals is something that is quite viewed by many people, regarding the legal status of a person who undergoes sex reassignment surgery, especially with marriage in Indonesia, and the District Court Decree (PN) provides guidance and explanation regarding this matter. The nature of God Almighty creates two sexes between male and female, along with the development of science and technology, especially in the field of medicine for those who experience conditions can also be called Sex Reassignment Surgey as a form of treatment in order to match their soul. Therefore, the researcher analyzes how Islamic law and national law regulate the legal status of transsexuals after sex reassignment and its implications for their rights and analyzes the procedure for sex reassignment and its impact. The stages of analysis use the descriptive method and deductive mindset. The results of this study conclude about the replacement of transsexual genitals in the consideration of the judge and granting the application in accordance with Islamic law and national law based on Law number 4 of 2004 written in article 28 paragraph 1.